Calvarial bone destruction secondary to dermoid cyst with squamous cell carcinoma transformation: A rare case report - Laksmi Indreswari; Novan Krisno Adji; Komang Yunita Wiryaning Putri; Muhammad Yuda Nugraha (International Journal on Health and Medical Sciences, 2026)
Dermoid cysts are congenital, benign lesions that originate from ectodermal inclusions during embryogenesis and are most often encountered in the scalp and intracranial regions. While their clinical course is generally indolent, malignant transformation is an exceptionally rare phenomenon, with squamous cell carcinoma (SCC) being the most frequently reported histologic subtype. Such transformation is clinically significant, as it alters the otherwise benign natural history of dermoid cysts into a locally aggressive neoplasm capable of extensive tissue invasion. We report a rare case of a dermoid cyst undergoing malignant degeneration into SCC with associated calvarial bone destruction. This case highlights the importance of recognizing atypical clinical presentations and radiologic findings that may suggest malignant change. The clinical manifestations, radiographic characteristics, surgical approach, histopathological confirmation, and postoperative course are presented, followed by a review of the relevant literature to contextualize this uncommon entity and its therapeutic implications.